2022
DOI: 10.1002/ange.202207410
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Hydrogenation with a Carbon‐Nitride‐Supported Palladium Single‐Atom Photocatalyst and Water as a Proton Source

Abstract: Dedicated to Professor Matthias Beller on the occasion of his 60th birthday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, g-C 3 N 4 is considered to have favorable application prospects due to its structural stability and low economic cost. Based on these advantages, g–C 3 N 4 –based SACs have been widely studied and remained a research hotspot over the past two years [ [30] , [31] , [32] , [33] ]. Moreover, it is also considered a favorable photocatalyst with good visible light response and suitable band gap, making it effective in photocatalysis [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, g-C 3 N 4 is considered to have favorable application prospects due to its structural stability and low economic cost. Based on these advantages, g–C 3 N 4 –based SACs have been widely studied and remained a research hotspot over the past two years [ [30] , [31] , [32] , [33] ]. Moreover, it is also considered a favorable photocatalyst with good visible light response and suitable band gap, making it effective in photocatalysis [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both experiments and theoretical calculations have shown that graphene-derived carbon compounds offer excellent promise as substrates for SACs. Graphene may be converted from a passive catalyst into one with excellent catalytic efficiency and selectivity by the insertion of metal single atoms (SAs) for CO2 reduction [46,47], activation of the C−H bond, selective hydrogenation [48], conversion of N2 (including electrochemical nitrogen reduction reaction (NRR)) [49], CO2 photocatalytic reduction reaction [50], and photocatalytic hydrogen evolution [51].…”
Section: Introductionmentioning
confidence: 99%